Der johanneische Auferstehungsbericht und die Überlieferung vom leeren Grab - Beutler, Johannes (Biblische Zeitschrift, 2022)
For John, Jesus’ exaltation on the cross and his exaltation to the Father coincide. From this perspective, a resurrection account could be missing. John adds it nevertheless in order to show the consequences of Jesus’ being exalted to the Father: Jesus brings from the Father God’s eschatological gifts. John uses the tradition of the earlier evangelists about the empty tomb, but in a critical way. This tradition belongs to the Synoptic Gospels as narrative texts and is influenced by early Jewish Apocalyptic and speculations about the raising of heroes of the past to God. The oldest traditions of the NT before and in Paul do not yet know this tradition.